E- learning: The school’s role in promoting inclusive education for children with special needs during covid-19 pandemic - Bustos, Ruth Claire; Tan, Emily (International Journal for Innovation Education and Research, 2021)
The Coronavirus Pandemic has brought about vast changes in the lives of people, from daily routines to social interactions. These abrupt changes hugely affected the education system, bringing about initiatives such as online classrooms and asynchronous activities. This scenario is tough for everyone, but it is more challenging to people with special needs and disabilities, particularly those who have Autism Spectrum Disorder and their families. Some mitigating factors that the government has imposed to curb the spread of the virus include social distancing and health protocols, contributing to the struggles faced by the children and their families. With the use of technology, E- Learning has been made possible.  Schools help lighten up the load by creating learning management system which acts as a replacement of traditional learning. Aside from children with disabilities, their parents or guardians should also be taught how to use the e-learning platforms for them to be effective partners of the teachers in guiding and nurturing these students. Through the literature review, this paper seeks to analyze the role of the school and the educators in promoting and fostering a culture of inclusivity for children with Autism Spectrum Disorder during the COVID-19 Pandemic outbreak, and to analyze how the Universal Design for Learning success model as an intervention that can support learners with special needs. The paper gives future directions for educators and researchers. Keywords: E-learning, Children with Autism Spectrum Disorder, Inclusion during COVID-19